2016
DOI: 10.1095/biolreprod.116.141945
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Uterine Epithelial and Conceptus Transcriptome and Luminal Fluid Proteome During the Peri-Implantation Period of Pregnancy in Sheep

Abstract: Studies support the idea that uterine epithelia and their secretions have important biological roles in conceptus survival, elongation, and implantation in sheep. The present study evaluated the transcriptome of the uterine luminal epithelium (LE) and glandular epithelium (GE) and the conceptus and proteome of uterine luminal fluid (ULF) during the peri-implantation period of pregnancy. Transcriptome (RNA-sequencing) analysis was conducted in LE and GE isolated from uteri of Day 10, 12, 14, 16, and 20 pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
73
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 96 publications
8
73
1
Order By: Relevance
“…Many studies have reported the role of IGF2BPs in cell proliferation, cell invasion, tumorigenesis, and embryogenesis [40][41][42][43][44][45][46][47][48][49][50][51]. IGF2BPs have also been found in sheep trophoblast cells suggesting their role in rapid proliferation of these cells [52]. HMGA1 promotes invasion of trophoblast cells and reduced levels of HMGA1 has been linked to pathogenesis of preeclampsia [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the role of IGF2BPs in cell proliferation, cell invasion, tumorigenesis, and embryogenesis [40][41][42][43][44][45][46][47][48][49][50][51]. IGF2BPs have also been found in sheep trophoblast cells suggesting their role in rapid proliferation of these cells [52]. HMGA1 promotes invasion of trophoblast cells and reduced levels of HMGA1 has been linked to pathogenesis of preeclampsia [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…The first important step in pregnancy recognition and implantation is interaction between the endometrial luminal epithelium (LE) and the blastocyst (Greening, Nguyen, Elgass, Simpson, & Salamonsen, ). In ruminant, the receptive endometrium and the elongation of the hatched blastocyst are required to complete the process of implantation (Brooks, Burns, Moraes, & Spencer, ). In particular, two‐thirds of failure pregnancy are due to abnormal uterine receptivity (Chen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, IFNT induces or substantially stimulates expression of several IFN‐stimulated genes (ISGs) which are speculated to involved in elongation and implantation of the conceptus in the ovine uterus, including ISG15 and chemokine (C‐X‐C motif) ligand 10 ( CXCL10 ) (Sakumoto et al, ). A recent study reports that the transcriptome of the uterine LE and GE was evaluated by laser capture microdissection in sheep, and genes abundantly expressed in the LE and GE during the peri‐implantation period of pregnancy included the radical S‐adenosylcontaining domain 2 ( RSAD2 ) and Osteopontin ( SPP1 ) (Brooks et al, ). With the development of blastocysts into filamentous conceptus during days 12–17, the conceptus of ovine gradually contact with LE and adhere firmly to LE on day 16 (Wan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have reported the successful transcriptome sequencing of multiple tissues in sheep brain 15 , uterus 16 , skeletal muscle 17–19 , mammary gland 20 , milk 21 , rumen 22 , and skin 23 tissues. To the best of our knowledge, only two transcriptomic studies on sheep have recently been conducted on large intestine metabolism.…”
Section: Introductionmentioning
confidence: 99%